Automation in the unloading and loading process of hot rolled coil using workspace simulation software : A Review - Kunal Abhay Patil; Santosh Jaju; Babu Achmare (Institute of Advanced Engineering and Science, 2016)
The aim of this paper is to confirm the importance of unloading and loading process of hot rolled coil and automation in manufacturing industry. This paper describes about the different systems which are used in various ISPAT industries for material handling purpose or lifting the heavy coils. There are six main systems which are used in industries for material handling purpose. After studying all these systems, we will propose one system which is more beneficial than other systems. Later in this paper we will also study the introductory part of the workspace simulation software, its features, benefits and applications. The objective of this project is to overcome the problems at industry by designing and simulating a robot arm to perform the task. By simulating, the process of unloading and loading of hot rolled coil can perform more effectively. Workspace LT is the software used in this project.